Det blot kulturelle - Butler, Judith (K&K - Kultur og Klasse, 2007)
Merely Cultural In this essay Judith Butler discusses the relationship between a ‘hard’ material Marxism and a ‘merely cultural’ cultural studies. Butler’s essay is a response to the attacks launched by feminists and Marxists against cultural studies and its apparent inability to focus on economic problems. Against those who distinguish between cultural and economic struggles Butler insists upon their entanglement avoiding the privilege given to each. Butler also argues that gay and lesbian struggles do indeed work against the reproduction of the entire capitalist system.